Epstein, Gerald. Busting the Bankers’ Club: Finance for the Rest of Us - Bruner, Robert F. (Journal of Economic Literature, 2025)
Robert F. Bruner of University of Virginia reviews “Busting the Bankers' Club: Finance for the Rest of Us” by Gerald Epstein. The Econlit abstract of this book begins: “Considers the financial crisis of 2007-09 and the financial reform response, promoting the argument that the source of both the intensity of the crisis and the weakness of the response was the power of a collection of big financial institutions and their supporters that acquired a huge amount of political power.”